Relação entre a habilidade de cuidado, sobrecarga, sintomas ansiosos e depressivos e qualidade de vida de cuidadores familiares de pessoas com doença renal crônica em hemodialise - Takimoto, Thaís Lieko de Oliveira (Universidade Federal de São Carlos, 2021)
The patient with chronic kidney disease (CKD) presents complications in relation to changes in his routine and consequently needs a family member who assists him/her in activities of daily living. To perform the function of caring the family member needs skill and competence. Prolonged involvement in the provision of care can have negative effects, such as overload, anxiety and depression, and may impact on your quality of life. Therefore, the aim of this study was to analyze the relationship between the ability of care and the perception of quality of life and the level of burden and anxiety and depressive symptoms of family caregivers of people with CKD on hemodialysis. This is a descriptive, correlational study with a quantitative approach, which was carried out in four renal replacement therapy units in the interior of the State of São Paulo. Family caregivers of hemodialysis patients participated in the study. After signing the Free and Informed Consent Form, the participants were interviewed individually with the application of the following instruments: Scale to measure the care ability of family caregivers of people with chronic disease (HCCF-DC Scale); Medical Outcomes Study 36- Item Short Form Health Survey (SF- 36); Caregiver Burden Scale (CBS); Hospital Anxiety and Depression Scale (HADS). Descriptive statistical and relationship analyses were performed between the variables collected. All ethical precepts have been respected. We evaluated 118 family caregivers and people with CKD, most of them women (75.4%), with an average of 50.966 (i.e., 50 years and 9 months). The dimensions relationship and change in the routine of the HCCF-DC Scale showed a negative, significant, moderate correlation with the anxiety and depression domains of the HADS instrument and weak, negative correlation between attitude and depression; dimensions relationship and change in the routine of the HCCF-DC Scale had a negative correlation, significant, of weak to moderate magnitude with overload, in all domains of the CBS; positive, significant correlation between the "Relationship" domain of HCCF-DC and all domains of the SF-36; Negative, significant, moderate correlation between the "Relationship" domain and HADS domains and CBS domains. The domain "Understanding" and the domain "Depression" (HADS), a negative, weak correlation was observed; in relation to the SF-36, the domains "Physical Aspects" and "General Health State" presented a positive and weak relationship. There was a negative, weak and moderate correlation between "Routine change" and between HADS and CBS (with significance in all HADS domains, CBS except the domain "Environment"); however, with the SF-36 domains, there was a weak to moderate positive correlation, and finally, the attitude domain had a negative and weak correlation correlated with HADS and CBS. It is concluded, therefore, that the higher the ability to care, the lower burden the caregiver presentes, and thus, better quality of lije.
Relationship between caring ability, burden, anxious and depressive symptoms and quality of life of family caregivers of people with chronic kidney disease undergoing hemodialysis
Keywords: Doença crônica; Cuidadores; Relações familiares; Qualidade de vida; Sobrecarga; Chronic Illness; Caregivers; Family relations; Quality of life; Overload; CIENCIAS DA SAUDE